PERANCANGAN PCB ECU PROGRAMABLE MESIN MATIC 125CC BERDASARKAN VARIASI ECU(ELECTRONIC CONTROL UNIT) - Fariz Hermawan, (2021)
The carburetor-based engine has been switched to a motorcycle system with a fully electronic system, basically the performance of the fuel injection engine is better than the conventional system. The ECU (Electronic Control Unit) functions as the center for ignition and electrical control in vehicles using the fuel injection system. Conventional ignition is a conventional ignition where the ignition still uses platinum as a breaker or ignition connector.Whereas for electronic ignition or those who have used a CDI or ECU, this ignition has used a transistor as an ignition coil circuit breaker, it doesn't mean there is no platinum, but it's just that its function is already not as a breaker or ptimer current connector but as a primary current switch. Programable ECU is an aftermarket product that has been chosen to improve engine performance, the difference in performance ranging from horsepower, torque, and the resulting top speed changes. The standard ECU produces 9.16 HP at 7,870 rpm and the programable ECU gets 9.23 HP at 5,490 rpm, the horsepower has increased by 0.7 HP. As for the torque generated by the standard ECU is 10.85 Nm at 5,260 rpm, while for programable ECUs it produces 11.93 Nm at 5,490 rpm for torque, it has increased by 1.08 Nm at 5,490 rpm.